NAEGLARIA FOWLERI: THE BRAIN EATING AMOEBA OR AN ENIGMA? - Mukhtar, Fatima; Wazir, Mohammad Salim (Journal of Ayub Medical College Abbottabad, 2015)
Naeglaria fowleri (N. fowleri), popularly known as the brain eating amoeba is the causative agent of the fulminant disease, primary amoebic meningoencephalitis (PAM). Although a rare disease, it is a threat to human health with a case fatality rate ranging from 95-99%. PAM cases have been reported from the United States of America, Australia, Europe and Asia. From 1962 to 2014, 133 people have been infected by N. fowleri in the USA, out of which only three have survived. None of the PAM cases reported in Pakistan so far has survived. This underscores the importance to identify factors, which have led to the failure in decreasing case fatality associated with N. fowleri despite major advances in medical technology, health care; and prevention and control strategies since the first reported case in 1965. We need to focus on eliciting risk factors of the disease prevalent in our part of the world, which are at variance with the developed world. A predominant number of PAM cases in the West are reported in young males who had participated in recreational activities. However, majority of cases reported in Pakistan are also among young males but they were linked with the religious practice of ablution. What is required to better understand and hence manage this enigma is further research. Further research is to be conducted to discover potent antimicrobials, to test the effectiveness of the new transcribial device in managing PAM, and to identify host factors, which make an individual susceptible to N. fowleri. Investigation of environmental factors related to N. fowleri also needs to be done. Doing so is of paramount importance, as it will help identify the preventive strategies to be employed against N. fowleri.